Dampak Budaya Organisasi Terhadap Kinerja Pegawai - Desvita Sekar Putri Kirani; Ajeng Syifa; Ira Riyani; Irma Niswatul Aini; Jasmine Sekar Hadi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article examines the impact of organizational work culture on employee performance by highlighting how the values and norms applied in the work environment can influence performance. work environment can affect employee performance employees. Through the literature study method, this research identifies elements of a positive work culture, including effective communication, team collaboration, and recognition of individual performance. recognition of individual performance. The results show that a supportive organizational culture can have a positive impact on improving employee performance. Of employees. By understanding the relationship between organizational culture and employee performance, companies can create a more positive environment to improve employee performance.